Risk Factors for Chronic Kidney Disease in Pediatric Patients with Epilepsy - Jun Pak; Jung Hye Byeon; Chung Hyuk Yim; Baik-Lin Eun (Korean Child Neurology Society, 2021)
Purpose The aim of the treatment of epileptic seizures is to achieve a seizure-free state without adverse effects. The mainstays of seizure treatment are anticonvulsant medication, diet therapy, and surgery. Antiepileptic drugs and a ketogenic diet are associated with various types of medical adverse effects, including chronic kidney disease (CKD). We aimed to identify the characteristics of pediatric epilepsy patients who developed CKD and to determine the possible mechanisms. Methods We included 816 patients who underwent medical treatment for epilepsy and were followed-up for at least 3 years at a tertiary hospital. The patients were divided into CKD and non-CKD groups. The data were assessed using a multivariate Cox proportional hazards model to identify the factors associated with CKD among patients undergoing epilepsy treatment. Results Initial high serum creatinine levels (hazard ratio [HR], 13.927; P=0.010), microscopic hematuria on initial urinalysis (HR, 10.047; P=0.001), developmental delay (HR, 11.929; P=0.000), and interictal epileptiform discharges on initial electroencephalography (generalized interictal epileptiform discharges: HR, 38.395, P=0.003; focal interictal epileptiform discharges: HR, 19.252, P=0.006) were associated with increased CKD risk. Conclusion CKD was more likely to develop in patients who presented with initial kidney dysfunction and developmental delay, and was related to epilepsy itself. The abovementioned factors may increase CKD risk through decreased brain function, which may lead to decreased activity and, hence, to relatively poor hygiene and voiding function. Moreover, patients with pre-existing kidney disease were more vulnerable to CKD development.